An assessment of critical carbon services and water resources in South Africa’s terrestrial protected area network - Plaistowe, Jonathan (Department of Biological Sciences, 2023)
Conservation planning can more greatly emphasise the importance of considering ecosystem services alongside biodiversity features to improve the planet's climate change resilience. Protected Areas (PAs) are a form of area-based conservation that successfully protects biodiversity and may conserve ecosystem services important for societal climate change resilience. This study assesses the performance of South Africa's protected area network in protecting strategic carbon and water services, which are important for climate change resilience. My first question investigated how well the country's PAs perform regarding the area coverage of carbon stocks and Strategic Water Source Areas (SWSA). My second question investigated whether the country's PAs have effectively protected the carbon stocks inside their borders. I hypothesised that the carbon stock values would be higher in PAs, given that PAs have successfully prevented the loss of natural land cover inside their borders. I also compared the effectiveness of PAs in protecting carbon stocks in terms of their management authority, province and land cover classes. I used existing datasets of PAs, environmental variables, SWSAs and carbon stocks for this study. Using the total organic carbon (TOC) and South Africa's Natural Land Cover, I calculated natural Strategic Total Organic Carbon Areas (STOCA). Then I used the STOCAs and SWSAs to assess the PA coverage of these two strategic ecosystem service areas and their overlapping areas. For the second question, I investigated the carbon stock values inside and outside PAs while controlling for environmental variables. I also investigated the effect of natural land cover, provincial designations and management authorities. Results indicate that South Africa's PAs cover 9.8% of the country's mainland but protect 14.8% of SWSAs, 21.7% of STOCAs and 28.5% of the SWSA & STOCA areas. The PAs have greater TOC, Total Soil Organic Carbon (TSOC) and Total Biomass Organic Carbon (TBOC) values inside their borders than outside. Natural areas inside PAs are higher in TOC, TSOC and TBOC values than outside natural or transformed areas. These results provide evidence that South Africa's PAs are effectively protecting their carbon stocks. Therefore, there is evidence that PAs are important for climate change mitigation and may be important for Nature-based Solutions (NbS) in increasing climate change resilience. Eastern Cape, KwaZulu-Natal, Limpopo, and Western Cape PAs should be studied to improve other PAs' management. Although the PA network is strategically placed to protect the country's ecosystem service areas, the extent of this protection is short of international PA targets. There are many more strategic ecosystem service areas available for protection. Considering the effectiveness of Eastern Cape and KwaZulu-Natal PAs and the availability of strategic ecosystem service areas for protection, policy-makers and conservation managers should consider these provinces for PA expansion. Limpopo should also be considered for PA expansion, given the high carbon stock values outside PAs. This study shows the importance of South Africa's protected area network for climate change resilience and provides information on where its necessary expansion can best be planned for. It also offers a potential set of metrics and targets for monitoring in the future.